2021
DOI: 10.1016/j.apsusc.2021.150060
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up microwave-assisted seed-mediated synthesis of gold nanoparticles onto nanocellulose to boost stability and high performance for SERS applications

Abstract: Bottom-up microwave-assisted seed-mediated synthesis of gold nanoparticles onto nanocellulose to boost stability and high performance for SERS applications,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…With this platform, preliminary results on the label-free screening of S protein were reported, through the identification of characteristic bands of proteins. 119 …”
Section: Paper-based Diagnostics For Viral Pathogen Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this platform, preliminary results on the label-free screening of S protein were reported, through the identification of characteristic bands of proteins. 119 …”
Section: Paper-based Diagnostics For Viral Pathogen Detectionmentioning
confidence: 99%
“…More recently, Marques et al reported a SERS platform based on a nanocellulose substrate, obtained from nata de coco cubes, with in-situ grown gold nanoparticles, assisted by microwave irradiation. With this platform, preliminary results on the label-free screening of S protein were reported, through the identification of characteristic bands of proteins 119.…”
mentioning
confidence: 99%
“…Moreover, the use of these substrates allows the production of sensing devices that are sustainable and recyclable . These substrates are very versatile and have been used in various applications, including the development of sensing devices based on optical or electrochemical measurements . The ZnO nanostructures are the basis of the developed glucose sensor, in which the addition of glucose to the nanorods is followed by UV irradiation, which stimulates the monosaccharide’s photo-oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease (COVID-19) has caused the global outbreak with millions of deaths, and the death toll is still rising. Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is the pathogen of COVID-19, which has an envelope structure and contains genetic substrate of single positive-stranded RNA [ [1] , [2] , [3] ]. The virus is a β coronavirus derived from bats, and phylogenetic studies have shown that it may infect humans and spread among human hosts through other intermediate hosts [ 4 ].…”
Section: Introductionmentioning
confidence: 99%